Pectoralis-II Myofascial Block and Analgesia in Breast Cancer Surgery: A Systematic Review and Meta-analysis. (September 2019) - Hussain, Nasir; Brull, Richard; McCartney, Colin J. L.; Wong, Patrick; Kumar, Nicolas; Essandoh, Michael; Sawyer, Tamara; Sullivan, Timothy; Abdallah, Faraj W.
Editor's Perspective: What We Already Know about This Topic: Pectoralis-II block is a potential alternative to paravertebral blocks to provide regional analgesia for breast cancer surgery What This Article Tells Us That Is New: This meta-analysis includes 14 randomized trials comparing pectoralis-II block with paravertebral blocks and found that there were no differences in pain scores or opioid consumption between the two groups in patients having surgery for breast cancer Pectoralis-II blocks were noninferior to paravertebral blocks in reducing pain intensity and morphine consumption for the first 24 h after surgery and both were superior to systemic analgesia alone Background: Thoracic paravertebral block is the preferred regional anesthetic technique for breast cancer surgery, but concerns over its invasiveness and risks have prompted search for alternatives. Pectoralis-II block is a promising analgesic technique and potential alternative to paravertebral block, but evidence of its absolute and relative effectiveness versus systemic analgesia (Control) and paravertebral block, respectively, is conflicting. This meta-analysis evaluates the analgesic effectiveness of Pectoralis-II versus Control and paravertebral block for breast cancer surgery. Methods: Databases were searched for breast cancer surgery trials comparing Pectoralis-II with Control or paravertebral block. Postoperative oral morphine consumption and difference in area under curve for pooled rest pain scores more than 24 h were designated as coprimary outcomes. Opioid-related side effects, effects on long-term outcomes, such as chronic pain and opioid dependence, were also examined. Results were pooled using random-effects modeling. Results: Fourteen randomized trials (887 patients) were analyzed. Compared with Control, Pectoralis-II provided clinically important reductions in 24-h morphine consumption (at least 30.0 mg), by a weighted mean difference [95% CI] of −30.5 mg [−42.2, −18.8] ( P < 0.00001), and in rest pain area under the curve more than 24 h, by −4.7cm · h [−5.1, −4.2] or −1.2cm [−1.3, −1.1] per measurement. Compared with paravertebral block, Pectoralis-II was not statistically worse (not different) for 24-h morphine consumption, and not clinically worse for rest pain area under curve more than 24 h. No differences were observed in opioid-related side effects or any other outcomes. Conclusions: We found that Pectoralis-II reduces pain intensity and morphine consumption during the first 24 h postoperatively when compared with systemic analgesia alone; and it also offers analgesic benefits noninferior to those of paravertebral block after breast cancer surgery. Evidence supports incorporating Pectoralis-II into multimodal analgesia and also using it as a paravertebral block alternative in this population. Abstract : This meta-analysis includes 14 randomized trials comparing pectoralis-II block with paravertebral blocks and found that there were no differences in pain scores or opioid consumption between the two groups in patients having surgery for breast cancer. Pectoralis-II blocks were noninferior to paravertebral blocks in reducing pain intensity and morphine consumption for the first 24 h after surgery and both were superior to systemic analgesia alone.Supplemental Digital Content is available in the text.